STRATEGI MEMBANGUN GLOBAL BRAND PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI (PTKIN) MENUJU WORLD CLASS UNIVERSITY - Hasanah, Siti Ma'rifatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Brand is a crucial element that gives great contribution to the success of an organization, both business and nonprofit organization. State Islamic Higher Education (PTKIN) needs to be aware to the value of branding and build a strong and sustainable Brand. Universitas Islam Negeri Maulana Malik Ibrahim Malang (UIN Maliki Malang) is one of PTKIN has tried several strategies to build global Brand toward world class university. This research tries to explain: 1) How strategic plan of UIN Maliki Malang Brand development towards world class university. 2) How the strategy is used by rector in building global brand toward world class university 3)How the management of international students in UIN Maliki Malang. This research uses a qualitative approach and case study type. Source of the data is derived from informants and documentation, which are adjusted to the research focus. The technique for data analysis uses interview, observation, and documentation. In analyzing the data, the researcher reduce and display the data then make the conclusion. For checking the data validity, source and method triangulation are also conducted. The results of this study indicate that: 1) UIN Maliki Malang strategic planning is formulated in University's Guideline (GBHU), which contains: that contain: integration of science and Islam, billingual, university policy, ma’had and HTQ, internationalization university, lecture and student’s development, revitalization socio and religious function through LP2M, faculties development, management development, fund rising. 2) Implementation of Global branding strategy towards world class university is doing segmentation in global scala, targetting, positioning and differentiation in global scala. Segmentation changed from national, regional and international, targetting changed, positioning and differentiation promoted globally to attract international students and international reputation. 3) International student in UIN Maliki Malang was come since 2009 until now. UIN Maliki Malang has one department focused in guiding and sharing about problems and difficulties from international student. Main problem that they faced are languange (bahasa Indonesia) and academic adaptation.